PENGARUH REVIEW PRODUK, KONTEN MARKETING DAN PERSEPSI HARGA PADA TIKTOK TERHADAP KEPUTUSAN PEMBELIAN CAMILLE BEAUTY BY NADYA SHAVIRA - Anggi Nurijayanti; MG. Sukamdiani; Dian Noor Citra Perdana (STIE Wijaya Mulya, 2023)
This study aims to determine the effect of product reviews, marketing content, and price perceptions on TikTok on purchasing decisions for Camille Beauty by Nadya Shavira. The data used is primary data collected from questionnaires to 100 respondents consumer Camille Beauty. With the sampling technique using random sampling. The data processing method uses the Multiple Linear Regression method. Based on the research results, the regression equation is obtained: Y = 1.290 + 0.198X1 + 0.905X2 + 0.182 X3 Based on statistical data analysis, the indicators in this study are valid and the variables are reliable. Individually, the variable that has the greatest influence is the Marketing Content variable with a regression coefficient of 0.905, followed by the Product Review variable with a regression coefficient of 0.198 and Price Perception with a regression coefficient of 0.182. Testing the hypothesis using the t test shows that the variables Product Review, Marketing Content and Perceived Price significantly influence the dependent variable on purchasing decisions, the Adjusted R Square number of 0.931 (93.1%) indicates that the purchasing decision variable can be explained by product review variables, content marketing and price perception. While the remaining 6.9% is explained by other variables outside the three variables used in this study such as product quality, brand image and others.